HUBUNGAN KARAKTERISTIK PEKERJA, PROMOSI K3, DAN KETERSEDIAAN ALAT PELINDUNG DIRI (APD) DENGAN PERILAKU TIDAK AMAN PADA PEKERJA MECHANICAL MAINTENANCE - Yunita Setiarsih; Yuliani Setyaningsih; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Unsafe Behaviour is an act of workers who deviate from the principle of the HSE and safe procedure, which can cause accidents. Around 88% accident in work place caused from unsafe action. Action can be affected by predisposing factor, enabling factor and reinforcing factor.The aim of this study was to identify the association of worker characteristic, safety promotion and PPE availability inmechanical maintenance worker with unsafe action.This type of research is cross sectional study with observasional study and analytic.Population of this research is mechanical maintenance workerstotaling 57 people, and the sample in this study using total population method. Data was measured by filling questioner by respondent and observation by researcher. Statistical analysis is using Chi- Square correlation test with the results showed there are no correlation between age, job status, education level, job tenure, and knowledge with unsafe action (p value ≥0,05). There are correlation between manner, supervision, training, and PPE availabilitywith unsafe action (p value <0,05). Company should give training to all workers,monitoring CSMS and KPI on contractor and give reward for workers that obedient and safe action.